Osteoporosis: genetic analysis of multifactorial disease - Zajickova, Katerina; Zofkova, Ivana (Endocrine regulations, 2003)
Osteoporosis is a common disorder with a complex pathophysiology involving both endogenous and environmental factors. Family and twin studies have shown that genetic factors play an essential role in bone mass regulation and that apart from rare instances the heritability of bone mineral density (BMD) and osteoporosis is polygenic. Linkage analysis and association studies with numerous DNA markers (single nucleotide polymorphisms or microsatellites) have analysed several bone-related candidate genes encoding vitamin D, calcium-sensing, calcitonin and estrogen alpha receptors, insulin growth factor I, collagen type I alpha 1 chain and others. Despite this, the definite polymorphic marker has not been found in different populations which reflects the divergent results of association studies with their frequent limitations, and probably the fact that the relevant polymorphism is still awaiting identification. Once the genetic determinants can be defined, the clinical implications would be extensive both in diagnostics and in pharmacogenetics.
Keywords: Animals; kolagen typu I, řetězec alfa 1; Humans; Multifactorial Inheritance; lidé; genetické markery; zvířata; genetická vazba; Collagen Type I, alpha 1 Chain; osteoporóza; multifaktoriální dědičnost; Genetic Linkage; Osteoporosis; Genetic Markers